2014
DOI: 10.1377/hlthaff.2013.1190
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies From Three States: Breaking Down Silos Between Health Care And Criminal Justice

Abstract: The jail-involved population-people with a history of arrest in the previous year-has high rates of illness, which leads to high costs for society. A significant percentage of jail-involved people are estimated to become newly eligible for coverage through the Affordable Care Act's expansion of Medicaid, including coverage of substance abuse treatment and mental health care. In this article we explore the need to break down the current policy silos between health care and criminal justice, to benefit both sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…13 Roughly half of justice-involved individuals are expected to be eligible for health insurance through the Affordable Care Act (ACA), 10,14 and many believe insurance expansion offers an opportunity to improve access to substance abuse and mental health treatment for this population. 5,14,15 One recent report suggested that the ACA improved insurance rates among justice-involved individuals with SUD. 16 However, to date, no national reports have assessed insurance trends among the general justice-involved population following implementation of either the ACA's dependent coverage mandate, which expanded parental health insurance to children age 19-25, 17,18 or Medicaid expansion and Marketplace plans.…”
Section: Introductionmentioning
confidence: 99%
“…13 Roughly half of justice-involved individuals are expected to be eligible for health insurance through the Affordable Care Act (ACA), 10,14 and many believe insurance expansion offers an opportunity to improve access to substance abuse and mental health treatment for this population. 5,14,15 One recent report suggested that the ACA improved insurance rates among justice-involved individuals with SUD. 16 However, to date, no national reports have assessed insurance trends among the general justice-involved population following implementation of either the ACA's dependent coverage mandate, which expanded parental health insurance to children age 19-25, 17,18 or Medicaid expansion and Marketplace plans.…”
Section: Introductionmentioning
confidence: 99%
“…After decades of public health–related entities working in separate silos, the landscape is evolving to take on a systems-wide approach that connects and coordinates public health–related services to care for and support entire populations (Bechelli et al, 2014; Public Health Foundation for the Performance Management National Excellence Collaborative, 2003). DrPH programs must adapt to this changing landscape and ensure that their graduates are prepared to serve as leaders in interdisciplinary settings (ASPPH, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative methods have a lot to offer, but the subfield has plenty of activity in qualitative research and mixed methods to address the complexity of the problems of interest. Health Affairs has published work using ethnographic analysis (e.g., Bhatia &Corburn, 2011), interviews andcontent analysis (e.g., Etchegaray et al, 2014), and regularly features case studies (e.g., Bechelli et al, 2014;Laurance et al, 2014;Lerner, Robertson, & Goldstein, 2015;Rosenbaum, Cartwright-Smith, Hirsh, & Mehler, 2012). The Milbank Quarterly has published studies using comparative (Sorenson & Drummond, 2014) and content analysis (Van der Wees et al, 2014), ethical (Rhodes & Miller, 2012) and critical interpretive analysis (Moat, Lavis, & Abelson, 2013), and has expanded its op-ed section to include additional informed commentary from leading health policy scholars.…”
Section: Methods For Modeling Complexitymentioning
confidence: 99%